Cloning and expression analysis of HSP70 gene from Dendrobium officinale under low temperature stress - Li, Dong-Bin; Gao, Han-Hui; Si, Jin-Ping; Zhu, Yu-Qiu (Zhongguo zhongyao zazhi, 2013)
To investigate HSP70 gene expression from Dendrobium officinale under low temperature stress, which will provide the molecular biological foundation for breeding the low temperature resistant strain. HSP70 gene full length cDNA was cloned by rapid amplification of cDNA ends (RACE) on the basis of HSP70 gene fragment sequences, and the structure and function of HSP70 gene were deduced. The expression of HSP70 under low temperature stress was detected by RT-PCR. The full length of HSP70 gene cDNA was 2 296 bp containing a 1 944 bp open reading frame (ORF) that encoded a protein of 647 amino acids. Its amino acids sequence had typical HSP70 characteristics and high homology with other plant's HSP70. Cold stress expression analysis showed that expression of the HSP70 gene could be induced by low temperature. The HSP70 gene of D. officinale was successfully cloned and reported for the first time which proved that the expression could be induced by low temperature. The cloning of HSP70 gene provides a stable foundation for further study of D. officinale cultivation and the breeding of the cold resistance strains.